Investigating possible wind energy potential to meet the power shortage in Karachi - Aman, M.M.; Jasmon, G.B.; Ghufran, A.; Bakar, A.H.A.; Mokhlis, Hazlie (Elsevier, 2013)
Electricity is always considered as an important ingredient for development of a country. Energy deficit affects the growth rate of the country and causes discomfort to the consumer. The power shortage in Karachi, the largest city and economical hub of Pakistan, is highly hampering the progress of the city. Presently the energy deficit in the city is around 328 MW. This paper presents an analytical analysis of incorporation of small residential windmills to reduce the power shortage in Karachi. To estimate the wind energy potential in the city, four years wind data is collected from Pakistan Metrological Department (PMD) at various heights (10 m, 30 m, 50 m, 75 m and 100 m). The statistical calculations on wind data using SPSS software show that the city has an enormous wind potential available. A case study is also carried to show the effect of incorporation of small residential wind mills in power system. The results shows 1678 MW h of energy could be saved if 50 of residential consumers are equipped with small windmills. The paper also discusses the possible resistance in the introduction of small residential windmills in domestic sector. The potential benefits to the utility and consumers are also presented in this paper.